Study of Jet quenching with Z+jet correlations in Pb-Pb and pp collisions at s NN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (American Physical Society, 2017)
The production of jets in association with Z bosons, reconstructed via the μþμ− and eþe− decay channels, is studied in pp and, for the first time, in Pb-Pb collisions. Both data samples were collected by the CMS experiment at the LHC, at a nucleon-nucleon center-of-mass energy of 5.02 TeV. The Pb-Pb collisions were analyzed in the 0%–30% centrality range. The back-to-back azimuthal alignment was studied in both pp and Pb-Pb collisions for Z bosons with transverse momentum pZ T > 60 GeV=c and a recoiling jet with pjet T > 30 GeV=c. The pT imbalance xjZ ¼ pjet T =pZ T, as well as the average number of jet partners per Z, RjZ, was studied in intervals of pZ T. The RjZ is found to be smaller in Pb-Pb than in pp collisions, which suggests that in Pb-Pb collisions a larger fraction of partons associated with the Z bosons fall below the 30 GeV=c pjet T threshold because they lose energy.